Electrocardiography in the Assessment of Right Ventricular Dysfunction and related Clinical Outcomes in Patients with pulmonary embolism - Sadeghi, Mohsen; Zarei, Negar; Kiani, Arda; Sharif-Kashani, Babak; Taghavi, Kimia; Abedini, Atefeh (Cardiology and Cardiovascular Medicine, 2019)
Introduction: Several studies have been done on the relationship between right ventricular (RV) dysfunction in pulmonary embolism and electrocardiographic changes in the Electrocardiography (ECG). Confirmation of such relationships will help early detection of pulmonary embolism and, as a result, reduce the need for thrombotic and aggressive therapies. The aim of this study was to determine the relationship between ECG changes and the clinical outcomes of patients with pulmonary embolism. Materials and Methods: Patients who referred to Masih Daneshvari Hospital during the year 2016 with acute dyspnea, chest pain and other symptoms associated with pulmonary embolism, and had embolism confirmed by Computed Tomography Angiography (CT angiography), in terms of symptoms Hemodynamic and echocardiographic disorders were studied. ECG results were compared with those of troponin I and previous uric acid found in the patient records, and the results were analyzed. Results: In this study, 83 patients with mean age of 51.5 ± 15.8 and 25 to 83 years old were studied. Of these, 64 (77.1%) were male and 19 (22.9%) were female. The mortality rate in the study was 6% and 6% (7%) needed surgery. Among the findings of the ECG, the relationship between RAD, ST depression, T preordial, Qr with RV dysfunction was significant (p <0.001, p = 0.007, p = 0.003, p <0.001). Also, RAD, ST depression, T preordial, Qr with secondary TR showed a significant relationship (p = 0.04, p = 0.03, p = 0.01, p = 0.001). There was a significant relationship between ST-depression and patient's mortality among ECG findings (p = 0.04). In addition, treatment with fibrinolytic and the need for surgery with RV dysfunction was significantly associated. Discussion: Electrocardiographic changes were associated with right ventricular dysfunc